42 The Impact of Home Respiratory Support on Developmental Outcomes in Very Preterm Infants. (19th August 2020) - McRae, Lindsay; Kieran, Emily; Luu, Thuy Mai; Shivananda, Sandesh; Synnes, Anne
Abstract: Introduction/Background: Bronchopulmonary dysplasia (BPD) is a common complication of extreme prematurity and may require prolonged home respiratory support. BPD is associated with worse neurodevelopmental outcomes but the impact of home respiratory support on neurodevelopmental outcomes, rehospitalization rates and association with caregiver sociodemographics is less well studied. Objectives: This study examines the impact of home respiratory support on neurodevelopmental outcomes in very preterm infants at 18-24 months corrected gestational age. Design/Methods: This linked Canadian Neonatal Network and Canadian Neonatal Follow-Up Network (CNFUN) multicenter cohort study of infants born April 1, 2009-December 31, 2016 at <29 weeks' gestational age assessed at 18-24 months corrected age at a CNFUN site compared significant neurodevelopmental impairment rates, rehospitalization rates and sociodemographics in children with and without home respiratory support using Chi-square and student t-tests. Results: Of the 3918 infants, 622 (15.9%) received home respiratory support. As expected, infants on home respiratory support had a lower gestational age (mean 25.5 vs 26.5 weeks, p < 0.01), lower birth weight (mean 781 vs 955 grams, p < 0.01), longer NICU stay (mean 118 vs 76 days, p < 0.01) and more comorbidities: late onset sepsis (35.1% vs 22.9%, p < 0.01), NEC ≥ stage 2 (8.9% vs 5.9%, p = 0.01), grade 3-4 IVH or PVL (12.7% vs 8.4%, p < 0.01) and ROP ≥ grade 3 (28% vs 10.8%, p < 0.01). Infants on home respiratory support had higher significant neurodevelopmental impairment rates defined as Bayley-III motor, cognitive, language scores <70, nonambulatory cerebral palsy (GMFCS ≥ 3), hearing and/or visual impairment rates (Table 1), rehospitalization rates (63.3% vs 29.2%, p < 0.01) and >3 rehospitalizations (19.8% vs 5.0%, p < 0.01). With home respiratory support, fewer families had paid employment and more were on social welfare. Conclusion: Children born preterm who are discharged home on respiratory support, compared to those without home support, are more likely to experience neurodevelopmental impairment and rehospitalization, and may have an adverse impact on family income. This is important for discharge planning and follow-up care of these high risk children.